Sacroiliitis and HLA. A clinical and genetical study. Issue 6 (December 1978) - Migone, N; Modena, V; Daneo, V; Carbonara, A O; Ceppellini, R
Abstract : Among 39 patients (23 males, 16 females) with sacroiliitis (SI) 17 were HLA-B27 positive. The female/male ratio in the B27-positive group was 2/15. Seventy-four first-degree relatives of 26 probands were also investigated. A high occurrence of SI (20%) was observed in the families of B27-positive probands compared with only 3.7% in the families of B27-negative probands. In the former families SI occurred only in B27-positive subjects with an earlier onset of symptoms and a male prevalence. In the latter, the disease showed a later onset and a lack of male preponderance. The nosological and prognostic relevance of the B27 typing is stressed.